Electroclinical features of myoclonic-atonic epilepsy - Deng, Jie (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2011)
OBJECTIVE: To summarize the electroclinical characteristics of myoclonic atonic epilepsy (MAE) in children